The Impact of Financial Statement Quality on Investment Decision Making: A descriptive study of the Banking Sector in West Java - Irwan Moridu (The Es Accounting And Finance, 2023)
The impact of the quality of financial statements on investment decision-making is a crucial area of research in the realm of finance. This descriptive study investigates this relationship in the banking sector of West Java, Indonesia. The research employs a combination of quantitative and qualitative methods, analyzing financial statements from selected banks and conducting surveys and interviews with investment decision-makers. The findings reveal that the majority of banks demonstrate consistent adherence to accounting principles, ensuring accurate and relevant financial information. However, concerns regarding the timeliness of financial reporting and comparability of financial statements were identified. Investment decision-makers emphasize the importance of financial statement quality in their evaluations, highlighting its role in building confidence and trust. High-quality financial reporting positively influences investment attractiveness. The study's implications suggest that enhancing financial statement quality can lead to improved investor confidence, reduced cost of capital, and increased transparency in the investment landscape. Future research can explore other sectors and regions, providing a more comprehensive understanding of this crucial relationship.